Simulation of Stratified Two-phase Flow Regime using Air-Water Model in ANSYS Fluent®. (November 2019) - Monachan, Binet; Thomas, Rijo J.; Steaphen, Deepak; Skaria, Mathew; Shafi, K.A.
Abstract: Two-phase flow has widely grown in importance in various fields of science and engineering system such as nuclear reactors, heat exchangers, transport system, chemical processing plants etc. One of the major issues faced by these sectors is the development of an accurate and reliable multiphase flow measurement system. At present there is no single system which could measure the two phase flow parameters irrespective of its incoming conditions. Characterization of the single phase flow parameter is easier when compared with two phase flow as the velocity distribution, mass flow rate and void fraction of each component phases are not easily measurable. The other factors that add to these difficulties are the prediction of flow regimes and the effect of pipe or channel orientation on the flow properties in the two phase flow. The hold-up of the individual phases and their relative velocity along with pressure drop needs to be taken care while dealing with these flows. Various researches have clearly shown that no correlation can be used for predicting the flow regimes in a two phase flow satisfactorily. By using volume of fluid multiphase flow model air water two phase flow was simulated for inlet velocities of water and air as 0.121 m/s and 6.56 m/s respectively. Stratified laminar flow was obtained from the CFD simulation. Variation in volume fraction of both air and water, mass flow rate and pressure drop with respect to change in time are investigated using the simulation.